1995
DOI: 10.1002/neu.480280102
|View full text |Cite
|
Sign up to set email alerts
|

Red‐light‐induced suppression of melatonin synthesis is mediated by N‐methyl‐D‐aspartate receptor activation in retinally normal and retinally degenerate rats

Abstract: Pineal gland N-acetyltransferase (NAT) activity and pineal and serum levels of melatonin declined linearly in albino rats acutely exposed to different intensities of red light (600 nm or higher; low, 140 microW/cm2; moderate, 690 microW/cm2; high, 1200 microW/cm2) during the middle of the night. The high intensity red light was as effective as white light (780 microW/cm2) in suppressing NAT activity and pineal and circulating melatonin. Red-light-inhibited nighttime NAT activity and suppressed nocturnal melato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

1998
1998
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 18 publications
(30 reference statements)
0
12
0
Order By: Relevance
“…At long wavelengths, previously published data are often contradictory regarding the inhibitory effects of LAN in some rodent species (Vanecek and Illnerova, 1982;Poeggeler et al, 1995;Hanifin et al, 2006), and in some data there is a lack of a well-defined pattern of effects (Cardinali et al, 1972;Brainard et al, 1984;Benshoff et al, 1987). Our results demonstrated no clear sensitivity in MLT levels of M. socialis to LAN at 679nm (red), indicating a marginal role for red-shifted retinal photoreceptors, such as NIFPRs, ) at three different wavelengths at increasing durations of acclimation (1day, 1week and 3weeks) starting from control levels.…”
Section: Discussion Upr and 6-smt Daily Rhythmsmentioning
confidence: 99%
“…At long wavelengths, previously published data are often contradictory regarding the inhibitory effects of LAN in some rodent species (Vanecek and Illnerova, 1982;Poeggeler et al, 1995;Hanifin et al, 2006), and in some data there is a lack of a well-defined pattern of effects (Cardinali et al, 1972;Brainard et al, 1984;Benshoff et al, 1987). Our results demonstrated no clear sensitivity in MLT levels of M. socialis to LAN at 679nm (red), indicating a marginal role for red-shifted retinal photoreceptors, such as NIFPRs, ) at three different wavelengths at increasing durations of acclimation (1day, 1week and 3weeks) starting from control levels.…”
Section: Discussion Upr and 6-smt Daily Rhythmsmentioning
confidence: 99%
“…The neuronal pathway from the retina to the SCN (via the retinohypothalamic tract) mediates the suppressive effect of light and the entrainment of the melatonin rhythm to the light/dark cycle (Moore and Lenn 1972). Previous studies have indicated that excitatory amino acids may be involved in photic entrainment of circadian rhythms and melatonin production (Cowell et al 1991;Ohi et al 1993;Poeggeler et al 1995). Further studies have shown that glutamate, the dominant excitatory neurotransmitter in the central nervous system, mediates photic entrainment (DeVries et al 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Pharmacological studies have revealed that antagonists of postsynaptic receptors that mediate the actions of this neurotransmitter block the light induced suppression of melatonin (Cowell et al 1991;Ohi et al 1993). Hypothalamic N -methyl-D -aspartate (NMDA) receptors coupled to a nitric oxide/cGMP signaling pathway have been identified (Amir 1992;Cowell et al 1990;Mikkelsen et al 1995;Poeggeler et al 1995). The observed supersensitivity to light in patients with BD and SAD may thus be related to a NMDA receptor mediated mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have indicated that excitatory amino acids may be involved in photic entrainment of circadian rhythms and melatonin production (Cowell et al, 1990 ;Mikkelsen et al, 1995 ;Ohi et al, 1993 ;Poeggeler et al, 1995). Further studies have shown that glutamate, the dominant excitatory neurotransmitter in the central nervous system mediates photic entrainment (DeVries et al, 1993).…”
Section: Discussionmentioning
confidence: 96%